A reference database of forensic autosomal and gonosomal STR markers in the Tigray population of Ethiopia. (January 2022) - Haddish, K.; Chierto, E.; Di Vella, G.; Lacerenza, D.; Raddi, S.; Aneli, S.; Bogale, A.L.; Kidane, E.; Yizengaw, A.; Getaneh, Y.; Tewelemedhin, G.; Kumar, H.R.S.; et al.
Abstract: Allele frequencies of 21 autosomal STR markers (AmpF/STR GlobalFiler) and haplotype frequencies of 27 Y- and 12 X-STR markers (AmpF/STR YFiler Plus and Investigator Argus X-12, respectively) were investigated in the Tigray population of Ethiopia, representing the main population group in the Tigray regional state of Ethiopia and neighboring Eritrea. For autosomal STR allele frequencies, the average random match probability in the Tigray sample was 2.1 × 10 -27 . The average locus by locus FST distance calculated comparing autosomal STR allele frequencies from Tigray and from a broad regional reference dataset currently available for the Horn of Africa was 0.003. The Tigray male sample displayed high Y-STR diversity, with complete individualization of haplotypes using the AmpF/STR YFiler Plus panel. Analysis of molecular variance did not detect significant heterogeneity between Y-STR haplotypes observed in the present study and those previously reported in the literature for other Tigray population samples from Ethiopia and Eritrea. Study of the X-STR landscape in Tigray evidenced several distinctive features including: the molecular characterization of a novel null allele at locus DXS10146 with frequency > 1%; allele dependency between loci within linkage groups I and III; significant differences in haplotype distribution compared to other Horn of Africa populations, that should be taken into account in kinship analysis. The collected data can be used as a reference STR database by local forensic genetics services and in genetic identification procedures of victims of human trafficking in the Mediterranean Sea, which frequently involve individuals originating from the Horn of Africa. Highlights: Forensic STR variation was investigated in the Tigray population of Ethiopia. Mean FST at aSTR loci between Tigray and other Horn of Africa populations was 0.003. High internal Y-STR haplotype diversity was found in the Tigray population. A novel null allele at locus DXS10146 with population frequency > 1% was identified. Data can aid genetic investigations of human trafficking in the Mediterranean Sea.